THE COMMAND TO FIGHT NON-MUSLIMS BASED ON HADITH PERSPECTIVE (THE MICRO AND MACRO ANALYSIS STUDIES) - Imran, Muhammad; Mahmud, Basri; Baba, Muammar; Taufani, Taufani (Jurnal Adabiyah, 2021)
This study aimed at comprehending Hadiths of ‘command to fight non-Muslims’. Understanding the hadith of the Prophet PBUH by using macro and micro approaches can avoid radicalism, intolerance, and even acts of terrorism. This research employed a qualitative descriptive by using the thematic analysis method. The researchers found that, in microanalysis studies of the hadith, there were 62 riwayahs with various lafaz variants, recorded in 8 kutub al-hadis (canonical and non canonical hadiths). The Hadiths’ command to fight non-Muslims' status was authentic both from the aspect of sanad and matn. Meanwhile, the macro analysis study of the hadith concluded that the practice of the hadith command to fight Non-Muslims must be understood in certain circumstances, not the generality lafaz of hadith. Textually, the hadith ‘command to fight non-Muslims’ can be applied if; 1) non-Muslims fought openly against Islam such as in the case of the Khaibar war, or 2) they refused the invitation of monotheism from the Prophet PBUH, such us what happened to the Bani Thaqif. After they were repulsed in the battle of Hunain, they fled to the Bani Taif area. Bani Tsaqif was besieged for 40 days, some of them surrendered and pledged to Islam. But if non-Muslims did not attack Muslims, or they made agreements in one country (mu'ahad), or they had the status of conquest and control of Muslims (dhimmi), then, their blood, soul, family, and property must be protected. The position of both non-Muslims and Muslims in the country was the same, they were citizens and the government must protect them. الملخص تهدف هذه الدراسة إلى وصف فهم الأحاديث حول "أمر محاربة غير المسلمين" عبر السياق الكلي والجزئي. في محاولة فهم الأحاديث النبوية عبر السياق الكلي والجزئي يمكنها أن تجنب فهم التطرف والتعصب وحتى أعمال الإرهاب. هذا البحث نوعي ووصفي باستخدام منهج التحليل الموضوعي. وجد هذا البحث أن الدراسة للأحاديث النبوية حول "أمر محاربة غير المسلمين" عبر السياق الجزئي ثَم اثنان وستون حديثا بألفاظ مختلفة مسجلة في ثماني كتب الأحاديث. الأحاديث حول "أمر محاربة غير المسلمين" صحيحة سندا ومتنا. أمر محاربة غير المسلمين يجب أن تُفهم من نواحٍ معينة، دون فهمها من حيث معاني ألفاظها العامة. يمكن تطبيق أحاديث "أمر محاربة غير المسلمين" نصيًا إذا؛ 1) قاتل غير المسلمين علنًا ضد الإسلام كما حدث في حرب خيبر، أو 2) كانوا مترددين في تلبية نداء التوحيد من النبي محمد صلى الله عليه وسلم، مثل ما حدث لبني ثقيف وذلك بعد صدهم في غزوة حنين حيث أنهم فروا إلى منطقة بني الطائف. كان بنو ثقيف محاصرين لمدة 40 يوما بعضهم استسلم وتعهد بالإسلام. ومع ذلك، إذا كان غير المسلمين لم يبدأوا في القتال، أو التزموا بالمعاهدة تحت مظلة الدولة الإسلامية، أو كانوا ذميون تحت سيطرة الدولة، فدمائهم وأرواحهم وأهاليهم وأموالهم محمية من قبل المسلمين. فإن وضعهم في نظر الإسلام كمسلمين أنفسهم، فهم يتمتعون بمكانة المواطنين الذين يجب حمايتهم.